Fuzzy sliding mode control with adaptive exponential reaching law for inverters in the photovoltaic microgrid - Pei, Xiugao; Zhao, Xinhua; Jia, Huiyong; Wang, Hao; Liu, Junpeng; Cheng, Hong; Yang, Yan (Frontiers in Energy Research, 2024)
Photovoltaic inverters are widely utilized in microgrid systems working as the key equipment for converting solar energy into usable electricity. This paper presents a fuzzy sliding mode control (FSMC) method for the photovoltaic inverter in a microgrid. The inverter module uses voltage control to achieve stable AC output voltage. Meanwhile, to deal with the system uncertainty and nonlinear in the photovoltaic inverter, a fuzzy controller was designed to realize real-time adaptation of the gains of the constant term and the reaching term in the sliding mode control law, which serves as a compensating controller for traditional sliding mode control. The gains of the exponential reaching law can be adjusted according to the system state instead of fixed gains, which can effectively reduce the chattering phenomenon and improve the robustness of the photovoltaic microgrid. Finally, the Lyapunov stability theory was used to ensure the stability of the entire control system, achieving a high-performance independent power supply for loads in a microgrid. Simulation results show that the designed control system is more robust to load disturbances, and has superior dynamic performance.